Islamophobia East-West and the politics of hospitality in contemporary Germany. Issue 1 (2nd January 2020) - Weber, Beverly
ABSTRACT: In this article I trouble the terms of hospitality and guest, as well as of east and west, in relationship to Islamophobia. In particular, I consider the graphic novel Im Land der Frühaufsteher, by Paula Bulling with sections written by Noël Kaboré. By focusing specifically on the notion of hospitality, I suggest that any narrative of racisms east/west cannot be disentangled into two separate stories, and that we should approach narratives of east/west difference with careful attention to the problematic premises on which they may rest. The necessary understanding of the workings of racism in contemporary Germany in order to challenge them relies on such a troubling. Furthermore, an exploration of refugee accounts of hospitality as they speak back to German 'welcome culture' opens up new possibilities for thinking through notions of hospitality, as well as the ways in which these possibilities are limited by racialization and racisms, including Islamophobia.